Conceptions of chemistry teachers about the evaluation theme (Research, Society and Development, 2023)
This research investigated the concepts that chemistry teachers in the metropolitan region of Belém and those working in high school had about learning assessment. The objective of the research was to seek the investigation of teachers as to what they thought about school evaluation and how they applied it with their students in the classroom. The research was qualitative and descriptive, involving 8 high school chemistry teachers in the metropolitan region de Belém with the application of a questionnaire with 12 questions, semi-open, online, made by the Google Forms platform and sent to teachers through social media, Instagram, WhatsApp and Telegram. The results were collected and transcribed in full, with the presentation of graphs that show the profile of the participants, such as age, graduation, gender and length of service. It was observed through the results obtained that teachers have formative conceptions of learning assessment in part of their speeches, in addition to considering assessment as a way of investigating student learning, through different methods or tools, whether traditional or alternatives.